Acute myeloid leukemia with T lymphoblastic lymphoma: a case report and literature review. Issue 5 (May 2021) - Gao, Yan; Feng, Xian-Qi; Liu, Shan-Shan; Xu, Yu-Jie; Mao, Chun-Xia; Li, Tian-Lan; Hou, Feng; Zhang, Wei
Acute myeloid leukemia (AML) with T lymphoblastic lymphoma (T-LBL) is a hematologic tumor of two origins, myeloid and lymphoblastic, and is relatively rare in the same patient. We report a rare case of AML with T-LBL. After the patient was diagnosed, he received standard chemotherapy, which decreased the primitive bone marrow cell percentage from 84% to 5%; however, the enlarged superficial lymph nodes showed no obvious change in size. Immunohistochemistry revealed the following: cluster of differentiation (CD)3 (+), CD5 (+), CD7 (+), transmission disequilibrium test (TDT) (+), myeloperoxidase (MPO) (−), and lysozyme (Lys) (−). The lymph node morphology and immunohistochemical results indicated T-LBL. Therefore, the final diagnosis was AML with T-LBL, with both diseases occurring independently and concurrently.